My lips are concealed: audio-visual speech enhancement through obstructions - Afouras, T; Chung, JS; Zisserman, A (ISCA, 2019)
Our objective is an audio-visual model for separating a single speaker from a mixture of sounds such as other speakers and background noise. Moreover, we wish to hear the speaker even when the visual cues are temporarily absent due to occlusion.